The problem of art in Plato's epistemology - ناصر, علاء (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
In this research, I tried to investigate a historical knowledge problem, which is the idea of ​​beauty and art, and what derives from it in terms of music, poetry, and other arts, in order to know its dimensions, this problem in its origins and in its historical sources. I played the problem of art with what it turned out to be in terms of presenting its subject from simulating and purifying the emotions of the individual and others, then I tried to investigate the reality of the dimensions of this problem in its cultural levels and its political, social and other meanings, so I discussed this problem between the two poles of the major knowledge in the history of philosophy, which is the problem of rational knowledge Which Plato came upon as the virtues of the individual and the state and sophism, which focused on the role of man in building sensory knowledge, so it focused on language in its phrases and verbal structures from which the case is composed according to the sophistic intent of rhetoric and its rulings under the pretext of convincing people of their linguistic skills that enable them to exercise their political functions .